Superalloys II - Birosca, Soran; Kolisnychenko, Stanislav (Trans Tech Publications, 2020)
The second volume of the topic series "Superalloys" contains articles published by Trans Tech Publications from 2018 up to 2019. This collection presents a wide range of scientific research results and engineering solutions in the field of alloy developments and performance, physical and mechanical properties, and processing technologies of various types of superalloys. We hope this collection will be beneficial and interesting to a broad audience of researchers and engineers from the area of materials science and engineering. Superalloys, Nickel-Based Superalloy, Thermal Properties, Mechanical Properties, Thermal Creep Deformation, Hot Corrosion, Microstructure, Solidification, Grain Boundaries, Single-Crystal Superalloy, Directionally Solidified Superalloy, Powder Metallurgy, Casting, Forging, Processing Technologies, Cutting, Drilling, Welding, Laser Processing, Rolling, Additive Manufacturing, Hot Extrusion, Electrical Discharge Machining, End Milling, Thermal Barrier Coatings, Bond Coat, Corrosion Protection, Vapor Deposition, Thermal Spraying, Modelling, Numerical Simulation Materials Science, Mechanical Engineering, Manufacturing
Keywords: Heat resistant alloys.; elektronické knihy; electronic books